2011
DOI: 10.1103/physrevc.84.044323
|View full text |Cite|
|
Sign up to set email alerts
|

Semimicroscopic description of backbending phenomena in some deformed even-even nuclei

Abstract: The mechanism of backbending is semi-phenomenologically investigated based on the hybridization of two rotational bands. These bands are defined by treating a model Hamiltonian describing two interacting subsystems: a set of particles moving in a deformed mean-field and interacting among themselves through an effective pairing force and a phenomenological deformed core whose intrinsic ground state is an axially symmetric coherent boson state. The two components interact with each other by a quadrupole-quadrupo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Previous works showed that there is a clear evidence for a major change in the nature of the ground state levels below I = 18 ћ in even-even nuclei in that region [1]- [8]. Furthermore, at higher spin values a very regular structure develops.…”
Section: Introductionmentioning
confidence: 92%
“…Previous works showed that there is a clear evidence for a major change in the nature of the ground state levels below I = 18 ћ in even-even nuclei in that region [1]- [8]. Furthermore, at higher spin values a very regular structure develops.…”
Section: Introductionmentioning
confidence: 92%
“…Also, in the Nilsson model, the last filled neutron state has = 1/2, while the last proton occupies the state = 7/2. The choice of the K = 1/2 sub-state as the Fermi level of the neutron system was made in [27] to describe the first backbending. As for considering the K = 7/2 Fermi level for the proton system, breaking the corresponding pair and aligning the resulting quasiparticle angular momenta to that of the core as prerequisite conditions of the second backbending, these features are in full agreement with the microscopic formalism used in the literature.…”
Section: The Model Hamiltonian and A Particle-core Product Basismentioning
confidence: 99%
“…In a previous publication [27], we proposed a semi-microscopic model for the description of the backbending phenomenon within the band-mixing picture. The rotational bands implied in the mixing procedure were defined by the angular momentum projection from quadrupole deformed product states and a model Hamiltonian describing a set of intruder neutrons interacting among themselves through pairing forces and coupled to a phenomenological deformed core.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations